Occupational Stress in Health Professionals of Combined Military Hospitals - Munir, Umar Rashed; Rahman, Md Fashiur; Ahsan, Mohammad Ahmed (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Stress is a term that is widely used in everyday life. Work-related stress is recognized globally as a major challenge to workers’ health and the health of an organization. Stress at work has become a serious problem affecting many people of different professions, life situation and age groups. The healthcare profession has been depicted as one of the most stressful occupations across the globe. Objective: To assess the extent of occupational stress among health professionals of Combined Military Hospitals and to explore its association with work-related factors and family-work interference. Materials and Methods: A total of 574 respondents were selected from five Combined Military Hospitals using simple random sampling considering doctors, nurses, paramedic medical assistants and technologists as the study population. Occupational stress was determined by Health Professions Stress Inventory (HPSI). Results: Stress of health professionals was reassessed through HPSI and 1.0%, 77.6%, 20.7% and 0.8% were found to be mild, moderate, very and extremely stressful respectively. About one fifth (21.4%) were found to be in high stress. High stress was more prevalent among Paramedic Medical Assistants (PMAs) (24.5%), Paramedic Medical Technologists (PMTs) (23.2%) and nurses (21.9%) on contrary to doctors (11.7%). Their mean stress scores were 55.70±13.75, 55.44±13.53, 56.18±10.55 and 50.92±10.93 respectively (p<0.05) out of 124. Highest stress was in CMH Dhaka (56.50±14.27) followed by CMH, Rangpur (53.43±11.65) (p<0.05). The mean work hour per week for doctors, nurses, PMAs and PMTs were 63.25(±18.95), 55.70(±9.72), 89.58 (±17.44) and 80.58 (±16.12) hours respectively (p<0.05). Working for long/unsociable or unpredictable hours, financial and job insecurity were found to be related to the greater prevalence of high stress (p<0.05). The parameters of pressures at work, job satisfaction and support from colleagues/superior were found to be associated with high stress (p<0.05). Higher prevalence of family-work interference was found to be a predictor of high stress (p<0.05). Conclusion: A large proportion health professional of Combined Military Hospitals were in high stress due to the prime stressors. Measures like workload-management, job-redesign, employee motivation and training should be taken to alleviate these stressors. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 37-41